Fuzzy Logic Implementation For Incubator Prototype With Temperature And Humidity Control - Arief Marwanto; Kuat Supriyadi; Suryani Alifah (IAES Indonesia Section, 2019)
Premature infant and young baby born with lowbody weight has potential to be in high risk and criticalcondition to survive. Medical equipment functioned as uterineis required, so the infant will have the similar condition as inthe womb of its mother. There is a need to control surroundingtemperature, humidity, oxygen supply, sound and light level tosupport the development of the infant's weight. Infants withlow weight have possibility to feel cold and have body heat loss.The use of additional supporting equipment such as incubatoris absolutely necessary and vital to create a stable surroundingenvironment for infant to keep the body temperature in rangeof normal and relatively constant value. In this paper, thefuzzy logic is implemented as the role of controller for anincubator equipped with temperature and humidity sensor.The propossed incubator prototype was tested in DR. SardjitoHospital, Yogyakarta Indonesia. The experiments showedprospected results to get a stable temperature and humiditywhich are suitable for premature baby.